A New Robot-assisted Billroth-I Reconstruction: Details of the Technique and Early Results. Issue 1 (February 2018) - Ceccarelli, Graziano; Marano, Luigi; Codacci-Pisanelli, Massimo; Andolfi, Enrico; Biancafarina, Alessia; Fabozzi, Massimiliano; Caruso, Stefano; Patriti, Alberto
Abstract : Background: Laparoscopic surgery for gastric tumor is considered a demanding procedure because of lymph node dissection and reconstruction. Billroth-I (B-I) reconstruction after laparoscopic distal gastrectomy is commonly performed extracorporeally because of the complexity of an intracorporeal procedure. Robotic surgery overcomes some limitations of laparoscopy, allowing to reproduce the basic maneuvers of open surgery. We describe a new technique to perform robotic B-I anastomosis. Methods: Between January 2012 and February 2015, 5 patients underwent distal gastrectomy with intracorporeal B-I-stapled anastomosis. Patient demographics, tumor characteristics, histopathologic features, and perioperative data were analyzed. Results: Median operative time was 170 minutes (145 to 180 min). There were no conversions. Contrast swallow was routinely performed on the third postoperative day. Median postoperative hospitalization was 7 days (range: 6 to 8). No major complications or mortality were observed. Conclusions: Robotic distal gastrectomy with intracorporeal B-I anastomosis is a safe and promising technique in selected cases of gastric tumors. Abstract : Supplemental Digital Content is available in the text.